Fabulous Khoisan:the politics of apoliticality in the indigenous Khoisan revivalism movement in South Africa; an exploration of sincerity,stickiness and fabulation in the emergence of a missing people - Wong, Eve (Department of Anthropology, 2025)
This dissertation critically reimagines postcolonial marginality, challenging the traditional 'before' and 'after' dichotomy to explore marginality as a dynamic, ongoing process of identity formation and resistance. Focusing on the Indigenous “Khoisan Revivalism” movement in South Africa, it examines how young, urban, and working-class individuals claiming Khoisan identity navigate intersections of cultural sincerity, political disengagement, and social justice. The work highlights the emergence of a resilient and marginalised “missing people.” whose identities are continuously shaped through historical struggles and contemporary aspirations. Rejecting essentialist notions of race, “mixedness,” and authenticity, this study positions “sincerity” as central to understanding identity production. Linking sincerity to Sara Ahmed's “stickiness” of affective flows and Gilles Deleuze's “fabulation” demonstrates how marginalised communities transform erased histories into tools for agency, actionable hope, and collective empowerment. Fabulation, in particular, enables the reimagining of suppressed identities, bridging historical realities with speculative futures. Tracing the historical contexts of “coloured” and “Khoisan” peoples, the dissertation troubles the boundaries of these definitions through interdisciplinary ideas. It reveals how gaps and incompleteness provide fertile spaces for identity reimaginings, offering fresh perspectives on how individuals claim and redefine belonging. Methodologically, the research combines ethnographic fieldwork, interviews, and cultural analysis while addressing the ethical complexities of representation. It also investigates how Khoisan identity is appropriated, authenticated, and politicised in legal frameworks, traditions, and state policies, exposing tensions between cultural revitalisation and sociopolitical alienation. With its focus on “cultural, not political” investments, the study challenges dominant, elite-driven identity discourses. By shedding light on South Africa's “missing people,” this work reframes marginalisation as a negotiation of identity and agency and a suspension between fear and desire. It is a compelling call to recognise the vibrancy and creativity of Khoisan revivalists as they reclaim belonging and craft new visions for social justice in an increasingly fragmented world.